Photoluminescence between 3.36 eV and 3.41 eV from GaN epitaxial layers - Seitz, R. (2012)
In this study, an attempt was made to analyze the luminescence between 3.36 eV and 3.41 eV of nid hexagonal GaN samples grown on sapphire. Sample dependent emission lines with no donor-accetor pair (DAP) behavior were found. Based on the data, different kinds of recombination processes in the same spectral region were identified.